Relationship Between Online Service Quality And Customer Satisfaction Among Online Banking Users In Malaysia - Allahverdi, Shahryar (2011)
This study attempts to determine the affects of the online service quality dimensions on customer satisfaction in Internet banking industry of Malaysia.